Association between Non-Alcoholic Fatty Liver Disease and Carotid Artery Intima-Media Thickness on B-Mode Ultrasonogram - Shams, Fahmida; Azam, Md Golam; Rabbi, Akanda Fazle; Rahman, Md Mizanur (Bangladesh Critical Care Journal, 2020)
Background: Prevalence of non-alcoholic fatty liver disease (NAFLD) is rapidly increasing worldwide. It is closely associated with abdominal obesity, dyslipidemia, hypertension, and type 2 diabetes, which are all features of the metabolic syndrome. Increased carotid intima media thickness (CIMT) is generally accepted as an early indicator of atherosclerosis and has been related to cardiovascular risk factors, and cardiovascular disease including incidence of myocardial infarction and stroke. The increasing rate of type II diabetes mellitus, abdominal obesity, sedentary life style and changes in the dietary habit, all are leading to serious health burden like NAFLD in Bangladesh. These patients have a higher risk of cardiovascular diseases. Early prediction of such incidence may help reduce the deadly consequences of NAFLD. Methods: This cross sectional study was carried out at the department of Radiology and Imaging of Dhaka Medical College and Hospital during the period of July 2015 to June 2017. Study population comprised of the outpatients who underwent abdominal ultrasonogram. Measurement of CIMT was done by high resolution real-time B-mode ultrasonogram at the same time. Body weight, height, blood pressure and available biochemical test reports were recorded along with a brief clinical history. Data were analyzed by SPSS version 23. Results: A total of 101 subjects were included in this study. Of them, on ultrasonographic examination of abdomen 49(48.5%) had normal liver assigned as group A and 52(51.5%) patients had fatty liver disease assigned as group B. Mean age of group A and group B patients were 36.8±12.4 and 46.15±10.3 years, and male:female ratio was 20:29 and 28:24 respectively. Family history of cardiovascular disease, diabetes mellitus and current smoking history were 14.3% versus 19.2%, 24.5% versus 44.2% and 14.3% versus 11.5% respectively among group A and group B. Frequency of NAFLD was grade I fatty liver 32.6%, grade II fatty liver 38.4% and grade I II fatty liver was 28.8%. Mean BMI was 24.8±4.1 versus 27.9±3.5 (p<0.001) and serum total cholesterol (mg/dl) was 175.1±41.3 versus 207.3±52.6 (P=0.030) among two groups. Both these parameters were significant. On the other hand mean systolic blood pressure (mm Hg) 127.5±16.1 versus 127.5±16.1 (P=0.836), mean diastolic blood pressure (mm Hg) 81.6±11.6 versus 82.4±8.7 (P=0.7.8), serum triglyceride level (mg/dl) 175.3±106.1 versus 213.4±167.4 (P=0.404) were not significant among groups. Mean CIMT (mm) was 0.62±0.15 in group A and 0.77±0.17 in group B (P<0.001) respectively. This result is highly significant. Accuracy of the CIMT in patients with or without NAFLD by ROC curve showed the area under curve (AUC) was 0.752 which was fair outcome of the study. CIMT cut-off at 0.680 mm showed the highest sensitivity (75%) and specificity (63%) for the presence of fatty liver disease by ultrasonogram. Conclusion: This study was aimed to explore the association between non-alcoholic fatty liver disease and carotid artery intima-media thickness on B-mode ultrasonogram. There is a positive correlation between NAFLD with CIMT. High BMI and raised serum cholesterol has significant role in the development of NAFLD. A large scale study is recommended to find more accurate cut off of CIMT in the relationship with NAFLD. Bangladesh Crit Care J September 2020; 8(2): 112-119